Bid responsive generation rescheduling for congestion management in electricity market. Issue 5 (12th November 2020) - Sarwar, Md; Siddiqui, Anwar Shahzad; Jaffery, Zainul Abdin; Kothari, D. P.
Abstract: Electricity market economics is one of the vital factors which play a key role in achieving the efficient operation of the power system. Economic operation along with secure & reliable operation is must for ensuring optimum utilization of the resources in order to maximize social welfare. This article presents a method for achieving economic operation of electricity market in case of congestion occurring in the system. The generator sensitivity (GS) method alone can manage the system congestion, however it does not consider the economic benefits which can be achieved by considering the bids submitted by the generators and as a result it leads to situation of market power. To avoid such scenario, bid sensitivity factor (BSF) is proposed to select the generators to participate and regulate their real power generation for alleviating congestion from the system optimally. The BSF takes into account the GS as well as bids of the generators. In this paper, the effectiveness of the proposed method in eliminating market power is realized by changing the bids of the generators. The proposed method is tested on IEEE 30‐bus system and IEEE 118‐bus system. The obtained results show an encouraging pattern for managing the congestion more optimally and economically. Abstract : The present work proposes a new methodology to reschedule the generators participating for congestion management based on generator sensitivity, as well as the bids submitted by the generators for rescheduling. The effectiveness of the proposed method in eliminating market power is realized by changing the bids of the generators. The proposed method is tested on the IEEE 30‐bus system and IEEE 118‐bus system, and the obtained results show an encouraging pattern for managing the congestion more optimally and economically.